2020
DOI: 10.1002/cam4.2984
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib vs platinum‐based chemotherapy as first‐line treatment for advanced non‐small cell lung cancer with different ROS1 fusion variants

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Our study has provided real-world clinical evidence on the efficacy of crizotinib in the first-line setting as reported in numerous clinical trials and other studies [ 8 , 13 , 14 , 21 23 ]. The clinical outcomes we have observed from the 168 crizotinib-treated patients were consistent with another study that reported the better ORR, DCR, and PFS with first-line crizotinib as compared to chemotherapy for ROS1 -rearranged NSCLC (ORR 80.0% vs 40.8%; DCR 90.0% vs. 71.4%; PFS 9.8 months vs 6.0 months) [ 21 , 24 ]. Moreover, our results that demonstrated better survival outcomes with first-line crizotinib for patients with non- CD74 ROS1 fusions than those who harbor CD74-ROS1 fusions (21.0 months vs 17.0 months) were consistent with a prior report that demonstrated a PFS of 17.6 months and 12.6 months, respectively [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study has provided real-world clinical evidence on the efficacy of crizotinib in the first-line setting as reported in numerous clinical trials and other studies [ 8 , 13 , 14 , 21 23 ]. The clinical outcomes we have observed from the 168 crizotinib-treated patients were consistent with another study that reported the better ORR, DCR, and PFS with first-line crizotinib as compared to chemotherapy for ROS1 -rearranged NSCLC (ORR 80.0% vs 40.8%; DCR 90.0% vs. 71.4%; PFS 9.8 months vs 6.0 months) [ 21 , 24 ]. Moreover, our results that demonstrated better survival outcomes with first-line crizotinib for patients with non- CD74 ROS1 fusions than those who harbor CD74-ROS1 fusions (21.0 months vs 17.0 months) were consistent with a prior report that demonstrated a PFS of 17.6 months and 12.6 months, respectively [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, our results that demonstrated better survival outcomes with first-line crizotinib for patients with non- CD74 ROS1 fusions than those who harbor CD74-ROS1 fusions (21.0 months vs 17.0 months) were consistent with a prior report that demonstrated a PFS of 17.6 months and 12.6 months, respectively [ 12 ]. Meanwhile, another study reported an opposite trend of longer PFS with crizotinib for patients with CD74-ROS1 than non- CD74-ROS1 (20.1 months vs. 12.0 months) [ 24 ], while no difference in PFS with chemotherapy was observed between CD74-ROS1 and non- CD74-ROS1 (8.6 months vs. 4.3 months) [ 24 ]. Since some of the ROS1 fusion partners are not as common as CD74 , survival outcome data for patients with these fusion partners remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of patients with ROS1 gene rearrangement is classical chemotherapy and/or targeted therapy, and the commonly used targeted drug is crizotinib. Scheffler’s study showed that 64.2% of patients with ROS1 gene rearrangement responded to chemotherapy, and the average overall survival (OS) of patients who received chemotherapy and crizotinib was estimated at 5.3 years ( 64 ), The results are somewhat consistent with the recently reported efficacy of crizotinib in the treatment of advanced NSCLC ( 65 , 66 ), recent studies have shown a change in the choice of treatment for patients with advanced ROS1 rearrangement in NSCLC. Patients with first-line selection of platinum-pemetrexed and crizotinib had different objective remission rates (85.1% vs. 86.7%) and progression-free survival (8.6 vs. 18.4 months), and there was no significant difference in OS (less than vs. 28.4 months) between the two groups ( 66 ).…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have focused on exploring the efficacy of TKIs among ALK, ROS1, and RET fusions with different partners and breakpoints. 10,35,36 We have previously found that patients with CD74-ROS1 fusion identified by DNA NGS who received first-line crizotinib have a longer PFS than patients with non-CD74-ROS1 fusion, 13 whereas Li et al 37 have observed diametrically opposite results. Moreover, at least 21 EML4-ALK variants have been described on the basis of breakpoint location, and these variants may be associated with clinical responses to TKIs.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 By applying DNA NGS, we have previously revealed that certain molecular biomarkers, such as EML4-ALK variants and concurrent TP53 mutations in ALK-rearranged cases and types of fusion partners in ROS1-rearranged cases, are associated with the efficacy of crizotinib. [11][12][13] In addition, we have found that some uncommon fusion variants of ALK, ROS1, and RET can be identified by DNA NGS, including noncanonical fusions harboring fusion partners that are rare or never reported (e.g., single non-EML4-ALK) and primary/reciprocal fusions harboring concurrent primary and reciprocal rearrangements. [14][15][16] Nevertheless, it remains unclear whether these special rearrangements can unequivocally produce the corresponding in-frame fusion transcripts, thus contributing to variable response to targeted therapy.…”
Section: Introductionmentioning
confidence: 96%